Renal Dietitians Lack Time And Resources To Collect And Analyze Dietary Intake Data - Rosa Hand; Alison Steiber; Jerrilynn Burrowes (The Korean Society of Nephrology, 2012)
Previous research indicated that renal dietitians lack the time and computer software to implement the KDOQI nutrition guidelines for assessing dietary intake. This study used an online survey to determine the frequency and method of collecting and analyzing dietary intake data among renal dietitians in the USA and overseas. The link to the survey was emailed to the members of the RenalRD listserve (n=2077), the International Society of Renal Nutrition and Metabolism (n=93), the Academy of Nutrition and Dietetics Renal Practice Group (n=2362), and the National Kidney Foundation Council on Renal Nutrition (n=1491). Only currently practicing renal dietitians were asked to respond; 599 usable responses were received. A response rate cannot be calculated due to membership overlap between the 4 organizations, although individuals were asked to answer only once. Respondents were 99% female, 91% worked in the USA, 45% had a M.S. degree or higher, and 21% were Board Certified Specialists in Renal Nutrition. Dietitians worked mostly in dialysis (hospital based facility 30%, Fresenius 18%, DaVita 17%) and 5% worked in a pre-dialysis CKD clinic. Median patient load was 120/Full Time Equivalent (inner quartile range 100-150). Dietitians reported that they collected dietary intake data most frequently when labs were abnormal (70%), yearly (41%), and at the first visit only (35%). They did not collect intake data more frequently due to lack of time (42%) and not having analysis software (24.9%). Only 10% of renal dietitians reported that the frequency of diet analysis was determined by following the KDOQI guidelines, while 58.5% reported deciding on their own when to collect data. The most common methods of data collection were the "typical day" recall (50%) and the 24-hour recall (37%). Only 8% reported using a 3-day food record (as recommended by KDOQI). Methods of diet analysis were "estimation in my head" (62%), "calculate by hand" (25%), computer software (6%) and internet analysis sites (7%). These data show that most dietitians are not following the KDOQI nutrition guidelines for frequency or method of diet analysis, and new, inexpensive, and rapid methods of diet assessment must be explored.